ENT 530 Social Media Portfolio / Siti Aisyah Husni - Husni, Siti Aisyah (2019)
Aqie Cruncheese expects to catch the interest of a regular loyal customer base with its delicious, affordable price with high quality products. This business plans to build a strong market position in the town, due to the product offers to people is different from others competitive out there. Aqie Cruncheese aims to offer its products at a competitive price to meet the demand